Sleep duration and cardiovascular disease: results from the National Health Interview Survey - Sabanayagam, Charumathi; Shankar, Anoop (Sleep (New York, N.Y.), 2010)
Previous studies have shown that both short and long sleep durations are related to increased likelihood of diabetes and hypertension. However, the relation between sleep duration and cardiovascular disease (CVD) is not clear. We examined the hypothesis that compared with sleep duration of 7 hours, shorter and longer sleep durations are independently related to CVD. We conducted a cross-sectional study of 30,397 National Health Interview Survey 2005 participants > or = 18 years of age (57.1% women). Sleep duration was categorized as < or = 5 hours, 6 hours, 7 hours, 8 hours, and > or = 9 hours. The main outcome of interest was the presence of any CVD (n = 2146), including myocardial infarction, angina, and stroke. We found both short and long sleep durations to be independently associated with CVD, independent of age, sex, race-ethnicity, smoking, alcohol intake, body mass index, physical activity, diabetes mellitus, hypertension, and depression. Compared with a sleep duration of 7 h (referent), the multivariate odds ratio (95% confidence interval) of CVD was 2.20 (1.78, 2.71), 1.33 (1.13, 1.57), 1.23 (1.06, 1.41), and 1.57 (1.31, 1.89) for sleep duration < or = 5 h, 6 h, 8 h, and > or = 9 h. This association persisted in subgroup analyses by gender, race-ethnicity, and body mass index categories. Also, similar associations were observed when we examined myocardial infarction and stroke separately. Compared with sleep duration of 7 h, there was a positive association between both shorter and longer sleep durations and CVD in a representative sample of US adults. These results suggest that sleep duration may be an important marker of CVD.